Relationship between aerobic and anaerobic parameters from 3-minute all-out tethered swimming and 400-m maximal front crawl effort - Kalva-Filho, Carlos A.; Zagatto, Alessandro Moura [UNESP]; Araujo, Monique I. C.; Santiago, Paulo R. P.; Silva, Adelino S. R. da; Gobatto, Claudio A.; Papoti, Marcelo (Lippincott Williams &wilkins, 2015)
The main aim of this investigation was to verify the relationship of the variables measured during a 3-minute all-out test with aerobic (i.e., peak oxygen uptake [VO(2)peak] and intensity corresponding to the lactate minimum [LMI]) and anaerobic parameters (i.e., anaerobic work) measured during a 400-m maximal performance. To measure force continually and to avoid the possible influences caused by turns, the 3-minute all-out effort was performed in tethered swimming. Thirty swimmers performed the following tests: (a) a 3-minute all-out tethered swimming test to determine the final force (equivalent to critical force: CF3-MIN) and the work performed above CF3-MIN (W'(3-MIN)), (b) a LMI protocol to determine the LMI during front crawl swimming, and (c) a 400-m maximal test to determine the VO(2)peak and total anaerobic contribution (W-ANA). Correlations between the variables were tested using the Pearson's correlation test (p <= 0.05). CF3-MIN (73.9 +/- 13.2 N) presented a high correlation with the LMI (1.33 +/- 0.08 m.s(-1); p = 0.01) and VO(2)peak (4.5 +/- 1.2 L.min(-1); p = 0.01). However, the W'(3-MIN) (1,943.2 +/- 719.2 N.s) was only moderately correlated with LMI (p = 0.02) and VO(2)peak (p = 0.01). In summary, CF3-MIN determined during the 3-minute all-out effort is associated with oxidative metabolism and can be used to estimate the aerobic capacity of swimmers. In contrast, the anaerobic component of this model (W'(3-MIN)) is not correlated with W-ANA.
Keywords: Critical force; Anaerobic work capacity; Force; Lactate minimum; Aerobic power